A evaluation of central components of the hearing organ in patients with chronic voice pathology - L. A. Lazareva; E. V. Baykina (Кубанский научный медицинский вестник, 2014)
A complex evaluation of central components of the hearing organ was performed using evoked brain stem potentials. We demonstrated a correlation of pathological processes in a voice producing system and in a hearing organ. The examination of short- and long-latency evoked brain stem potentials in patients with functional and organic voice dysfunction revealed changes in the brain stem structures, as well as in the cortex. It was demonstrated that more pronounced changes in the hearing organ can be found in patients with organic nature of voice deterioration.